Effect of bilastine on chronic spontaneous urticaria refractory to other antihistamines. Issue 2 (5th March 2019) - Inui, Shigeki
Abstract : Bilastine 20 mg/d was administrated for 18 patients with chronic spontaneous urticaria refractory to usual dose of other antihistamines for more than two weeks. As results, bilastine showed excellent effect for 13 patients (72.2%).